(untitled) (Government and Statistics, 2022)
This study analyzes the effect of exchange rates, money supply and interest rates on economic growth with inflation as the mediation, the data is secondary data for 2015 - 2021. The data sources are from the official website of BI (www.bi.go.id) and BPS (www.bps. go.id). Methods of data analysis using multiple linear regression analysis, hypothesis testing either partially or simultaneously. The results of the analysis show 1) there is a negative and significant effect between the exchange rate variable and the inflation variable. 2) there is a positive and significant effect between the money supply and interest rate variables and the inflation variable. 3) there is a positive and significant effect between the exchange rate and money supply variables with the economic growth variable. 4) there is no impact of interest rates and inflation on economic growth. 5) there is an impact of exchange rates, money supply, interest rates and inflation on economic growth. 6) inflation mediates the effect of the money supply and interest rates on economic growth.